Imaging Mild Cognitive Impairment and Dementia in Parkinson's Disease - Sasikumar, Sanskriti; Strafella, Antonio P. (Frontiers in Neurology, 2020)
Cognitive dysfunction is a significant non-motor feature of Parkinson’s disease, with the risk of dementia increasing with prolonged disease duration. Multiple cognitive domains are affected, and the pathophysiology cannot be explained by dopaminergic loss alone. Sophisticated neuroimaging techniques can detect the nature and extent of extra-nigral involvement by targeting neurotransmitters, abnormal protein aggregates and tissue metabolism. This review identifies the functional and anatomical imaging characteristics that predict cognitive impairment in PD, the limitations that challenge this process, and the avenues of potential research.